Formal Techniques for Distributed Objects, Components, and Systems 35th IFIP WG 6.1 International Conference, FORTE 2015, Held as Part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, Grenoble, France, June 2-4, 2015, Proceedings - Graf, Susanne; Viswanathan, Mahesh (Programming and Software Engineering, 2015)
This book constitutes the proceedings of the 35th IFIP WG 6.1 International Conference on Formal Techniques for Distributed Objects, Components and Systems, FORTE 2015, held in Grenoble, France, in June 2015, as part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015. The 15 revised full papers presented were carefully reviewed and selected from 53 submissions. The papers present a wide range of topics on distributed computing models and formal specification, testing, and verification methods.